USING DIGITAL TECHNOLOGIES IN EDUCATION - Ashurova, Sitora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article discusses using digital technologies in teaching processes. In the process of active learning of students in educational institutions, teachers should find ways to increase the level of involvement of students in the learning process, increase their motivation to use digital technologies. By using digital technologies students are taught how to use technology responsibly and strategically, which can help them make decisions and develop self-discipline. Technology in education can help students to prepare for lifelong learning.